Electrically modulated photothermal force microscopy for revealing molecular conformation changes during polarization switching at the nanoscale - Songyou Yao; He Jiang; Jiaxuan Wen; Da Shu; Chang Xu; Wenpeng Zhu; Xiaoyue Zhang; Yue Zheng (Nature Communications)
Abstract Organic ferroelectrics have attracted extensive attention because of the broad tunability of polarization via chemical and structural modifications. However, simultaneous analysis of the evolution of chemical and polarization properties at the nanoscale remains a challenge, impeding the understanding of their origin. In this work, we report electrically modulated photothermal force microscopy (ePTFM), an atomic force microscopy (AFM)-based technique that integrates nanoscale analysis of polarization with chemical specificity. By characterizing electrodriven ferroelectric switching in edge-on poly(vinylidene fluoride-co-trifluoroethylene) (P(VDF-TrFE)) lamellae, ePTFM reveals not only the evolution of polarization but also in situ chemical correlations. The results show that ePTFM has less electrostatic interference than conventional AFM techniques do, allowing intrinsic characterization of polar evolution under bias. Furthermore, via multi-wavenumber analysis, we propose a conformational mechanism for chain-direction ferroelectric switching in face-on P(VDF-TrFE). The proposed ePTFM provides fresh insight into polarization evolution and paves the way for mechanistic studies of polar organics.